Implementation of Student Teams Achievement Divisions (STAD) technique: Impact on undergraduate students' English speaking skill - Fitriyasni, Fitriyasni (ACCENTIA: Journal of English Language and Education, 2020)
The aim of this study was to investigate whether there was any significant difference in speaking improvement between using Student Teams Achievement Divisions (STAD) and non STAD. The study used the experimental research method and was conducted to the second year students at STAI Tapaktuan of 2017/2018 academic year with an experimental group of 19 students and a control group 20 students, selected through random sampling. Data came from pre-test and post-test which were analyzed by using t-test. The results showed that there was a significance difference in speaking improvement between the students who were taught by using STAD and those who were not. The result of t-test of the post-test was 0.00, (p-value0.05), indicating that H0 was rejected and H? was accepted.